Dampak Asesmen Diri Terhadap Karakter dan Literasi Ilmiah Siswa Kelas IV Sekolah Dasar - Ni Putu Kusuma Widiastuti; I Wayan Lasmawan (Mimbar Ilmu, 2022)
The implementation of the 2013 curriculum in Indonesia has not been carried out optimally. This study aims to analyze the differences in the implementation of self-assessment on character education and students' scientific literacy. The population of this study amounted to 192 students and the sample amounted to 21 students. Sample selection was done by simple random sampling technique. This research is quasi-experimental research (quasi-experimental) with Single Factor Independent Group Design. The data collection technique used a questionnaire for character and a test for scientific literacy. Data were analyzed using Manova. The results showed that the first hypothesis test value of F = 5.313 with a significance of 0.000 <0.05, which means that there are differences in the character of students who take part in learning with the implementation of self-assessment with students who take part in learning with the implementation of conventional assessments. The results of the second hypothesis test show that F = 5.233 with 0.000 <0.05, which means that there are differences in the scientific literacy of students who take lessons with the implementation of self-assessment and students who take lessons with the implementation of conventional assessments. The third hypothesis test shows that F = 1.660 with 0.000 <0.05 which means that there are differences in the character and scientific literacy of students simultaneously between students who take lessons with the implementation of self-assessment and students who take lessons with the implementation of conventional assessments.